2018
DOI: 10.4110/in.2018.18.e20
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-32 Gamma on Bone Metabolism in Autoimmune Arthritis

Abstract: IL-32 acts as a pro-inflammatory cytokine by inducing the synthesis of inflammatory molecules as well as promoting the morphological changes involved in the transformation of monocytes into osteoclasts (OCs). Evaluation of the functions of IL-32 has mainly focused on its inflammatory properties, such as involvement in the pathogenesis of various autoimmune diseases. Recently, IL-32 was shown to be involved in bone metabolism, in which it promotes the differentiation and activation of OCs and plays a key role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…IL‐32 has nine isoforms generated by alternative splicing 11,12,15 . The four most researched isoforms IL‐32α, IL‐32β, IL‐32γ, and IL‐32δ were first described in IL‐2‐stimulated human NK cells 4 12,47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐32 has nine isoforms generated by alternative splicing 11,12,15 . The four most researched isoforms IL‐32α, IL‐32β, IL‐32γ, and IL‐32δ were first described in IL‐2‐stimulated human NK cells 4 12,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The four most researched isoforms IL‐32α, IL‐32β, IL‐32γ, and IL‐32δ were first described in IL‐2‐stimulated human NK cells 4 12,47 . Among these isoforms, IL‐32α is the shortest and the least active pro‐inflammatory variant contains three protein domains, domains 1, 6, and 11 that consist of 131 amino acid residues 9,15,24 . Compared to other isoforms, IL‐32 α is also the most ample cDNA clone 8 and it is expressed in various cells such as NK cells, T cells, and monocytes 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides new prognostic information that can be used to further improve the current risk stratification strategy for MM patients. Kwon et al[17] reported that poor prognosis in patients with inflammatory diseases and autoimmune diseases had higher IL-32 expression. In a separate study, high expression of IL-32 was also found to be positively associated with metastasis and recurrence of renal cell carcinoma and gastric cancer[18].…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 is generally considered to be an inflammatory cytokine since early IL-32 research suggested that it is an inducer of TNFα. Therefore many investigators approached the effect of IL-32 in Th1 autoimmune-associated diseases such as rheumatoid arthritis, inflammatory bowel disease, and psoriasis (5678). The majority of clinical studies depend on the measurement of circulating IL-32 levels in the plasma or serum of patients comparing to normal individuals.…”
Section: Il-32 Variants In Different Diseasesmentioning
confidence: 99%